Phytochemicals screening and antioxidant activities of Malaysian Donax grandis extracts - Mohd Daud, Jamaluddin; Mohd Hassan, Husna Hawa; Hashim, Ridzwan; Taher, Muhammad (EuroJournals Publishing, Inc., 2011)
Common Donax (Donax grandis) is in a family of marantaceae and widely distributed in South East Asia region. Phytochemical constituents in different parts of the plant (leaves, fruits, stems and roots) were extracted by soxhlet extractions using hexane,dichloromethane, methanol and water. Methanolic extract showed the highest yield of crude extracts from all parts of the plant as compared to the other solvents, including water. Screening tests of the crude extracts revealed the presence of phenolic compounds, alkaloids, tannins, phytosterols, cardiac glycosides, terpenoids, steroids, saponins and flavonoids. Proximate analysis of saponins have also been done for all plant parts of D.grandis using the methanolic extract. The results showed that fruits contained the highest amount of saponins (2.39 wt.%). All parts of the plant samples showed highest total phenolic content (0.18 to 0.65 mg GAE/g). These three solvent fractions possessed strong radical scavenging activity from DPPH, in the ranged from 14.86 to 21.85 mg/mL. The results indicate that D. grandis is a potential candidate to be used as an antioxidant and antiproliferative agents.